The Cuban missile crisis : october 1962 the U.S. and Russia face a nuclear showdown - Cook, Fred J (New York : F. Watts, 1972)
Describes the events that precipitated the 1962 Cuban missile crisis and analyzes the steps taken by President Kennedy to avert the threat to the security of the western hemisphere.
Keywords: Military bases, Soviet -- Cuba -- Juvenile literature; United States -- Foreign relations -- Soviet Union -- Juvenile literature; Soviet Union -- Foreign relations -- United States -- Juvenile literature; Cuba -- History -- 1959 -- Juvenile literature